Maoist movement in India / Muzaffar H. Syed and M.K. Waseen - "Syed, Muzaffar" (New Delhi, 2013)
A powerful ideological force, though many people may always disagree with it, in ideology and practice, Maoism, also known as Mao Zedong Thought, is a political theory, derived from the teachings of the Chinese political leader, Mao Zedong. Its followers, known as Maoists,consider it as an anti-Revisionist form of Marxism-Leninism.
Keywords: Revolutionary movements-India